2016
DOI: 10.1016/j.neuropsychologia.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of quantifiers and object nouns in speech in focal neurodegenerative disease

Abstract: Quantifiers such as many and some are thought to depend in part on the conceptual representation of number knowledge, while object nouns such as cookie and boy appear to depend in part on visual feature knowledge associated with object concepts. Further, number knowledge is associated with a frontal-parietal network while object knowledge is related in part to anterior and ventral portions of the temporal lobe. We examined the cognitive and anatomic basis for the spontaneous speech production of quantifiers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 69 publications
(141 reference statements)
0
21
0
Order By: Relevance
“…However, on the assumption that patients use words with which they are more familiar in a semistructured speech sample, the more frequent use of verbs than nouns in svPPA would be contrary to the claim that the meaning of all words is degraded in svPPA. Likewise, we have showed that the meaning of words for abstract nouns is relatively preserved in svPPA (Bonner et al, 2016; Cousins et al, 2016) and that the meaning of words dependent on number knowledge is relatively preserved in svPPA (Ash et al, 2016). In a longitudinal study of lexical expression in svPPA, we found progressively reduced use of concrete words relative to abstract words (Cousins et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…However, on the assumption that patients use words with which they are more familiar in a semistructured speech sample, the more frequent use of verbs than nouns in svPPA would be contrary to the claim that the meaning of all words is degraded in svPPA. Likewise, we have showed that the meaning of words for abstract nouns is relatively preserved in svPPA (Bonner et al, 2016; Cousins et al, 2016) and that the meaning of words dependent on number knowledge is relatively preserved in svPPA (Ash et al, 2016). In a longitudinal study of lexical expression in svPPA, we found progressively reduced use of concrete words relative to abstract words (Cousins et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Finally, svPPA patients appear to have relatively preserved knowledge of number concepts and numerosity (Cappelletti et al 2001, Crutch & Warrington 2002, Halpern et al 2004, Jefferies et al 2004), although some investigators have also noted difficulty with number knowledge in svPPA patients who are quite impaired ( Jefferies et al 2005). svPPA patients also have relatively preserved knowledge of the class of words that depend on numbers, like ‘most,’ ‘less than half,’ and ‘few,’ known as quantifiers (Ash et al 2016, Cappelletti et al 2006). While additional research is needed to fully understand the representation of object concepts in semantic memory and the degradation of these concepts in svPPA, these findings suggest that object concepts are particularly vulnerable in svPPA.…”
Section: Semantic Variant Primary Progressive Aphasiamentioning
confidence: 99%
“…Spontaneous speech is often used to validate different neuropsychiatric attributes (11)(12)(13)(14)(15)(16) . But if multiple items representative of spontaneous speech are used, and it is also observed that the patient presents, for example, aphasia, subjecting him/her to the same failure over and over again can be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, many psychological attributes are evaluated or validated on the basis of spontaneous speech (11)(12)(13)(14)(15)(16)(17)(18)(19) , considered as a key attribute. However, there are few studies on the validity of spontaneous speech itself, in particular, on how it is perceived by caregivers in adults with acute aphasia.…”
Section: Introductionmentioning
confidence: 99%